SISTEM INFORMASI GEOGRAFIS PEMETAAN PERMASALAHAN DESA - Feryan Hadipurwanto; Dedi Trisnawarman; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
The purpose from this writing is to make an application that mapping issues in Sumbersari Village, the existing issues in here are natural disasters, dry season which never end, brawl, or typhoon. The purpose not just discuss about existing problem but also discuss about village profile, total population, village program development however the main writing is about mapping issues, results to be achieved is that when we mapping about the problem and display it in website. the information that we given can be useful to village government and villagers. The word useful here that we can help government to tell that there is problem here in the village and need to be look after and resolved. As for the Research Methods, The method used is Survey and  Secondary. The data that already obtain was from Books. The final result is this website can provide useful information to Government about existing problem and to villagers and the problem can be resolved quickly. The other information like total information can be useful to Sumbersari Village to be more developed than before.